Diabetes mellitus and its causes and treatment. - Djuraeva Zilola Aramovna; Khairullayeva Mukhlisa Lutfullayevna; Badriddinov Nu'mon Muhiddinovich; Mingbayev Anvar Abduvahobovich; Karshibayev Bekzod Yoldoshevich (Zien Journals, 2023)
This article provides information about diabetes mellitus and its causes and treatment.
Keywords: Diabetes; blood sugar level; insulin hormone; glucose